Water-based binder as well as preparation method and application thereof

By grafting reaction of acid anhydride and polyvinyl alcohol in a low eutectic solvent, the modified polyvinyl alcohol water-based binder is solved, and the problems of weak connection mode, high cost and large environmental pollution of the existing lithium-ion battery binder are achieved, and the efficient bonding, environmental protection and excellent electrochemical properties of lithium batteries are achieved.

CN119505750AActive Publication Date: 2025-02-25CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311060963.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-02-25
Estimated Expiration
2043-08-22

AI Technical Summary

Technical Problem

The binders of existing lithium-ion batteries, such as PVDF, have problems with weak connection methods, high costs and large environmental pollution, and the water-based binders that have been studied have shortcomings in electrochemical performance and environmental protection.

Method used

By grafting the acid anhydride and polyvinyl alcohol in the presence of a low eutectic solvent, a modified polyvinyl alcohol aqueous binder is prepared, which has good dispersion properties, compatibility, adhesion and environmental protection.

Benefits of technology

This water-based adhesive can significantly improve the bonding performance between the active substance and the conductive agent, reduce the internal impedance of the battery, improve the cycle stability and high-rate performance of the lithium battery, and extend the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505750A_ABST
    Figure CN119505750A_ABST
Patent Text Reader

Abstract

The invention relates to a water-based binder and a preparation method and application thereof, the water-based binder comprises modified polyvinyl alcohol, the modified polyvinyl alcohol has repetitive units shown as a formula (1) and a formula (2), # imgabs0 #, R1 is selected from one or more of-Ph and-Ph-(R3) n1, each R3 is the same or different, and n is a positive integer. The two groups are independently selected from one or more of halogen atoms and C1-C3 halogenated alkyl, and n1 is any integer between 1 and 5. The modified polyvinyl alcohol water-based binder disclosed by the invention has good dispersion performance on an electrode material and a conductive agent, keeps good compatibility with an electrolyte, and has the advantages of excellent cohesiveness and environment friendliness, so that the lithium ion battery further has excellent cycling stability and high rate performance, and the lithium ion battery has a wide application prospect. Therefore, the service life of the lithium battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of lithium ion battery binders, and in particular, to a water-based binder and a preparation method and application thereof. Background Art

[0002] Binder is one of the important components of lithium-ion batteries. Its main function is to tightly bond the active material and conductive agent to the electrode current collector to maintain the integrity of the electrode structure. Although the amount of binder used is small, its performance will directly affect the electrochemical performance and service life of lithium-ion batteries.

[0003] One of the current development trends of battery pole pieces is to use water-based binders to replace oily binders such as PVDF to make the lithium battery production process meet environmental protection requirements. At present, commercial lithium batteries use PVDF with 1-methyl 2-pyrrolidone (NMP) as a solvent as a binder. PVDF has the following disadvantages as a binder. First, the connection between PVDF and the active material is through weak van der Waals forces, and there may be separation between the active material and the current collector during the cycle; in addition, PVDF is expensive, and NMP is a high-boiling point toxic and flammable solvent with high recycling costs and greater environmental pollution.

[0004] Researching new water-based binders to meet the development needs of lithium-ion batteries has certain practical application value. The water-based binders that have been studied and reported are mainly polyacrylic acid (PAA), carboxymethyl cellulose (CMC), and sodium alginate; CMC has general bonding performance, high brittleness, and the pole piece is easy to crack during charging and discharging. PAA has a high glass transition temperature and is relatively hard at room temperature, which easily leads to hard and brittle pole pieces. In addition, PAA has poor viscosity and needs to be used with a thickener. CN115172752A reports a tannic acid and its derivatives as a water-based binder. The bonding strength and structural stability of the silicon-based negative electrode are significantly improved, but the battery has a high first-cycle discharge capacity and a low capacity retention rate, that is, the first-cycle discharge capacity and capacity retention rate cannot maintain the best performance at the same time. In addition, natural polymer materials such as sodium alginate and chitosan as binders have good environmental performance and good water solubility, but they have many shortcomings in electrochemical properties, bonding properties, etc., and it is difficult to meet the application requirements of batteries. Summary of the invention

[0005] The purpose of the present disclosure is to provide an aqueous binder and a preparation method and application thereof, wherein the aqueous binder has good dispersibility for electrode materials and conductive agents, maintains good compatibility with electrolytes, and has the advantages of excellent adhesion and green environmental protection.

[0006] In order to achieve the above object, the present disclosure provides a first aspect of an aqueous binder, comprising modified polyvinyl alcohol, wherein the modified polyvinyl alcohol has repeating units as shown in formula (1) and formula (2),

[0007]

[0008] Wherein, R1 is selected from one or more of -Ph and -Ph-(R3)n1, each R3 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n1 is any integer between 1 and 5.

[0009] Optionally, the weight average molecular weight of the modified polyvinyl alcohol is 50,000 to 300,000; and the molar content of ester groups in the modified polyvinyl alcohol is 5 to 15%.

[0010] Optionally, the aqueous binder is obtained by modifying polyvinyl alcohol with anhydride, wherein the anhydride has a structural formula as shown in formula (3),

[0011]

[0012] Wherein, R2 is selected from one or more of -Ph and -Ph-(R4)n2, each R4 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n2 is any integer between 1 and 5; preferably, R4 is selected from one or more of F and Cl, preferably F; and the C1-C3 halogenated hydrocarbon group is selected from one or more of -CF3, -CHF2 and -CH2F, preferably -CF3.

[0013] Optionally, the R3 is selected from one or more of F and Cl, preferably F; the C1-C3 halogenated hydrocarbon group is selected from one or more of -CF3, -CHF2 and -CH2F, preferably -CF3.

[0014] A second aspect of the present disclosure provides a method for preparing an aqueous binder, the method comprising:

[0015] Polyvinyl alcohol and anhydride are contacted and reacted in the presence of a low eutectic solvent; the anhydride has a structural formula as shown in formula (3),

[0016]

[0017] Wherein, R1 is selected from one or more of -Ph and -Ph-(R3)n1, each R3 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n1 is any integer between 1 and 5;

[0018] R2 is selected from one or more of -Ph and -Ph-(R4)n2, each R4 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n2 is any integer between 1 and 5;

[0019] R1 and R2 are the same or different.

[0020] Optionally, the alcoholysis degree of the polyvinyl alcohol is 88% to 99%, and the weight average molecular weight of the polyvinyl alcohol is 50,000 to 300,000, preferably 100,000 to 200,000;

[0021] The acid anhydride is one or more of benzoic anhydride, tetrafluorobenzoic anhydride and 4-trifluoromethylbenzoic anhydride; preferably one or more of tetrafluorobenzoic anhydride and 4-trifluoromethylbenzoic anhydride;

[0022] The mass ratio of the polyvinyl alcohol to the acid anhydride is 1 to 5:1, preferably 1.5 to 3:1.

[0023] Optionally, the low eutectic solvent comprises a hydrogen bond acceptor and a hydrogen bond donor; the hydrogen bond acceptor is a quaternary ammonium salt, and the quaternary ammonium salt is selected from one or more of choline chloride and benzyltriethylammonium chloride, preferably choline chloride;

[0024] The hydrogen bond donor is selected from one or more of amide, carboxylic acid, urea, thiourea and imidazole, preferably amide and urea; the amide is selected from one or more of formamide, benzamide and trifluoroacetamide, preferably benzamide; the carboxylic acid is selected from one or more of oxalic acid and levulinic acid, preferably oxalic acid;

[0025] The molar ratio of the hydrogen bond acceptor to the hydrogen bond donor in the deep eutectic solvent is 1:1-5, preferably 1:1-3.

[0026] Optionally, the contact reaction conditions include: being carried out in an organic solvent, the contact reaction temperature is 30 to 70° C., preferably 40 to 60° C.; the contact reaction time is 2 to 6 hours, preferably 3 to 5 hours; the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.

[0027] A third aspect of the present disclosure provides an aqueous binder prepared by the method described in the second aspect of the present disclosure.

[0028] A fourth aspect of the present disclosure provides use of the aqueous binder described in the first aspect or the third aspect of the present disclosure in a lithium ion battery.

[0029] Optionally, the aqueous binder is used for positive electrode sheets and / or negative electrode sheets of lithium-ion batteries.

[0030] Through the above technical scheme, the present invention obtains a modified polyvinyl alcohol aqueous binder by grafting anhydride and polyvinyl alcohol in the presence of a low eutectic solvent. The aqueous binder can enhance the bonding performance between the active material and the conductive agent as well as between the active material and the current collector, thereby ensuring the integrity of the electrode structure; it maintains good compatibility with the electrolyte, is beneficial to the transmission of electrons and ions inside the electrode sheet, greatly reduces the internal impedance of the battery, and improves the high rate performance and cycle stability of the positive and negative electrode materials of the lithium battery.

[0031] Other features and advantages of the present disclosure will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0032] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0033] A first aspect of the present disclosure provides an aqueous binder, comprising modified polyvinyl alcohol, wherein the modified polyvinyl alcohol has repeating units as shown in formula (1) and formula (2),

[0034]

[0035] Wherein, R1 is selected from one or more of -Ph and -Ph-(R3)n1, each R3 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n1 is any integer between 1 and 5.

[0036] The present invention uses polyvinyl alcohol for modification to improve the dispersibility and suspension of the slurry, which is beneficial to improving the quality and uniformity of the slurry; the aqueous binder of the present invention has a large number of active group hydroxyl groups, which can form strong hydrogen bonds with active materials and current collectors to improve their bonding strength; the aqueous binder of the present invention has a large number of benzene rings, which can generate π-π stacking interactions with the conductive agent, which is beneficial to improving the dispersibility of the conductive agent in the aqueous solution system, improving the conductivity of the electrode, and thus improving the high-power performance of the battery; the introduction of hydrophobic groups can reduce the hydrophilicity of the binder, improve the compatibility of the binder with the electrolyte, improve the interface compatibility problem, and at the same time reduce the polarity of polyvinyl alcohol, so that the electrolyte quickly enters the interior of the electrode, improves the conductivity of lithium ions, and further enables the lithium-ion battery to have excellent cycle stability and high-power performance; the present invention uses water-soluble polymer material polyvinyl alcohol for modification, which is green and environmentally friendly, low in cost, and easier to implement in engineering design.

[0037] According to one embodiment of the present disclosure, the weight average molecular weight of the modified polyvinyl alcohol is 50,000 to 300,000; and the molar content of ester groups in the modified polyvinyl alcohol is 5 to 15%.

[0038] According to one embodiment of the present disclosure, the aqueous binder is obtained by modifying polyvinyl alcohol with anhydride, wherein the anhydride has a structural formula as shown in formula (3),

[0039]

[0040] Wherein, R2 is selected from one or more of -Ph and -Ph-(R4)n2, each R4 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n2 is any integer between 1 and 5; preferably, R4 is selected from one or more of F and Cl, preferably F; and the C1-C3 halogenated hydrocarbon group is selected from one or more of -CF3, -CHF2 and -CH2F, preferably -CF3.

[0041] According to an embodiment of the present disclosure, the R3 is selected from one or more of F and Cl, preferably F; the C1-C3 halogenated hydrocarbon group is selected from one or more of -CF3, -CHF2 and -CH2F, preferably -CF3. The above preferred embodiment is conducive to the water-based binder having excellent bonding strength, swelling performance and lithium ion conductivity, further improving the cycle performance and high rate performance of the battery.

[0042] A second aspect of the present disclosure provides a method for preparing an aqueous binder, the method comprising:

[0043] Polyvinyl alcohol and anhydride are contacted and reacted in the presence of a low eutectic solvent; the anhydride has a structural formula as shown in formula (3),

[0044]

[0045] Wherein, R1 is selected from one or more of -Ph and -Ph-(R3)n1, each R3 is the same or different, and is independently selected from one or more of halogen atoms and C1~C3 halogenated hydrocarbon groups, and n1 is any integer between 1 and 5; R2 is selected from one or more of -Ph and -Ph-(R4)n2, each R4 is the same or different, and is independently selected from one or more of halogen atoms and C1~C3 halogenated hydrocarbon groups, and n2 is any integer between 1 and 5; R1 and R2 are the same or different.

[0046] The method disclosed in the present invention obtains a water-based binder by modifying polyvinyl alcohol with anhydride by means of chemical grafting in the presence of a low eutectic solvent, which is beneficial for the water-based binder to have excellent bonding strength, swelling performance and lithium ion conductivity, and further improves the cycle performance and high-rate performance of the battery.

[0047] According to one embodiment of the present disclosure, the alcoholysis degree of the polyvinyl alcohol is 88% to 99%, and the weight average molecular weight of the polyvinyl alcohol is 50,000 to 300,000, preferably 100,000 to 200,000. The alcoholysis degree of polyvinyl alcohol in the present disclosure refers to the maximum amount of polyvinyl alcohol that can be dissolved in water under specific conditions. The above-mentioned embodiment is conducive to making the water-based binder have excellent bonding strength, swelling performance and lithium ion conductivity, further improving the cycle performance and high rate performance of lithium batteries, and extending the service life of lithium-ion batteries.

[0048] According to an embodiment of the present disclosure, the acid anhydride is one or more of benzoic anhydride, tetrafluorobenzoic anhydride and 4-trifluoromethylbenzoic anhydride, and more preferably one or more of tetrafluorobenzoic anhydride and 4-trifluoromethylbenzoic anhydride. The above embodiment is conducive to making the water-based binder have excellent bonding strength, swelling performance and lithium ion conductivity, further improving the cycle performance and high rate performance of the lithium battery, and extending the service life of the lithium ion battery.

[0049] According to one embodiment of the present disclosure, the mass ratio of the polyvinyl alcohol to the acid anhydride is 1 to 5: 1, preferably 1.5 to 3: 1. The above embodiment is conducive to making the aqueous binder have excellent bonding strength, swelling performance and lithium ion conductivity, further improving the cycle performance and high rate performance of the lithium battery, and extending the service life of the lithium ion battery.

[0050] According to one embodiment of the present disclosure, the low eutectic solvent includes a hydrogen bond acceptor and a hydrogen bond donor; the hydrogen bond acceptor is a quaternary ammonium salt, and the quaternary ammonium salt is selected from one or more of choline chloride and benzyltriethylammonium chloride, preferably choline chloride; the hydrogen bond donor is selected from one or more of amide, carboxylic acid, urea, thiourea and imidazole, preferably amide and urea; the amide is selected from one or more of formamide, benzamide and trifluoroacetamide, preferably benzamide; the carboxylic acid is selected from one or more of oxalic acid and levulinic acid, preferably oxalic acid. The present disclosure does not impose specific restrictions on the amount of the low eutectic solvent, which can be the conventional amount in the art, for example, the mass ratio of the low eutectic solvent to polyvinyl alcohol can be 1:5. The above preferred embodiment is conducive to making the aqueous binder have excellent bonding strength, swelling performance and lithium ion conductivity, further improving the cycle performance and high rate performance of the lithium battery, and extending the service life of the lithium ion battery.

[0051] According to one embodiment of the present disclosure, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor in the low eutectic solvent is 1: (1 to 5), preferably 1: (1 to 3). In a further embodiment, the method includes: mixing the hydrogen bond acceptor and the hydrogen bond donor at a first temperature to obtain a low eutectic solvent. The first temperature is 60 to 80°C, preferably 65 to 75°C. The above-mentioned embodiment is conducive to making the aqueous binder have excellent bonding strength, swelling properties and lithium ion conductivity, further improving the cycle performance and high rate performance of the lithium battery, and extending the service life of the lithium ion battery.

[0052] According to an embodiment of the present disclosure, the conditions of the contact reaction include: being carried out in an organic solvent, the temperature of the contact reaction is 30 to 70°C, preferably 40 to 60°C; the time of the contact reaction is 2 to 6 hours, preferably 3 to 5 hours; the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone. The above embodiment is conducive to making the water-based binder have excellent bonding strength, swelling performance and lithium ion conductivity, further improving the cycle performance and high rate performance of lithium batteries, and extending the service life of lithium-ion batteries.

[0053] According to one embodiment of the present disclosure, the method includes: mixing polyvinyl alcohol with an organic solvent at a second temperature; the second temperature is 60 to 90°C, preferably 70 to 90°C. In a further embodiment, polyvinyl alcohol is dissolved in a contact solvent under oil bath conditions. The above embodiment is conducive to making the water-based binder have excellent bonding strength, swelling performance and lithium ion conductivity, further improving the cycle performance and high rate performance of lithium batteries, and extending the service life of lithium ion batteries.

[0054] The third aspect of the present disclosure provides an aqueous binder prepared by the method described in the second aspect of the present disclosure.

[0055] A fourth aspect of the present disclosure provides use of the aqueous binder described in the first aspect or the third aspect of the present disclosure in a lithium ion battery.

[0056] According to one embodiment of the present disclosure, the aqueous binder is used for positive electrode sheets and / or negative electrode sheets of lithium-ion batteries.

[0057] In one embodiment, the aqueous binder is used for a negative electrode plate of a lithium-ion battery, and the negative electrode plate includes a negative electrode current collector and a negative electrode solid coating loaded on the negative electrode current collector; the negative electrode solid coating includes a negative electrode active material, a conductive agent, and the modified polyvinyl alcohol aqueous binder described in the third aspect of the present disclosure. The present disclosure does not impose any specific restrictions on the negative electrode current collector, which can be a conventional material in the art, such as copper foil. The present disclosure does not impose any specific restrictions on the negative electrode active material, which can be conventional graphite, silicon dioxide, and silicon in the art. The present disclosure does not impose any specific restrictions on the conductive agent, which can be conventional conductive carbon black, carbon nanotubes, and graphene in the art, such as carbon black.

[0058] In one embodiment, the aqueous binder is used for a positive electrode plate of a lithium-ion battery, and the positive electrode plate includes a positive electrode current collector and a positive electrode solid coating loaded on the positive electrode current collector; the positive electrode solid coating includes a positive electrode active material, a conductive agent, and the modified polyvinyl alcohol aqueous binder described in the third aspect of the present disclosure. The present disclosure does not specifically limit the positive electrode current collector, which can be a conventional material in the art, such as aluminum foil. The present disclosure does not specifically limit the positive electrode active material, which can be conventional lithium iron phosphate or lithium cobalt oxide in the art.

[0059] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.

[0060] The polyvinyl alcohol used in the present disclosure is purchased from Aladdin Company, and the product number is P434371. Unless otherwise specified, the other reagents are commercially available products.

[0061] The electrochemical performance of the battery was tested on a CT2001A blue power test system.

[0062] Example 1

[0063] (1) taking appropriate amounts of choline chloride and urea in a molar ratio of 1:2, stirring and heating at 74°C until the solid is dissolved and becomes a transparent liquid, thereby obtaining a deep eutectic solvent;

[0064] (2) Take 1g of polyvinyl alcohol (weight average molecular weight of 200000, degree of alcoholysis 99%) in 10ml of dimethyl sulfoxide solution, heat and stir at 80°C until dissolved; after complete dissolution, add 0.5g of benzoic anhydride and 1ml of low eutectic solvent, heat and stir at 50°C for 4h; the mass ratio of benzoic anhydride to polyvinyl alcohol is 1:2. After the reaction is completed, the product is washed with ethanol to obtain a white flocculent substance, which is dried at 80°C for 12h to obtain a modified polyvinyl alcohol water-based adhesive.

[0065] Example 2

[0066] The method of this embodiment is the same as that of embodiment 1, except that benzoic anhydride is replaced by tetrafluorobenzoic anhydride.

[0067] Example 3

[0068] The method of this embodiment is the same as that of embodiment 1, except that benzoic anhydride is replaced by tetrakis-trifluorobenzoic anhydride.

[0069] Example 4

[0070] The method of this embodiment is the same as that of embodiment 1, except that the amount of benzoic anhydride added is 1 g, and the molar ratio of benzoic anhydride to polyvinyl alcohol is 1:1.

[0071] Example 5

[0072] The method of this embodiment is the same as that of embodiment 1, except that the amount of benzoic anhydride added is 0.25 g, and the mass ratio of benzoic anhydride to polyvinyl alcohol is 1:4.

[0073] Example 6

[0074] The method of this embodiment is the same as that of embodiment 1, except that the deep eutectic solvents choline chloride and urea are replaced by choline chloride and formamide.

[0075] Example 7

[0076] The method of this embodiment is the same as that of embodiment 1, except that the deep eutectic solvents choline chloride and urea are replaced by choline chloride and benzamide.

[0077] Example 8

[0078] The method of this embodiment is the same as that of embodiment 1, except that the deep eutectic solvents choline chloride and urea are replaced by choline chloride and imidazole.

[0079] Example 9

[0080] The method of this embodiment is the same as that of embodiment 1, except that the weight average molecular weight of the polyvinyl alcohol is 50,000 and the alcoholysis degree is 99%.

[0081] Example 10

[0082] The method of this embodiment is the same as that of embodiment 1, except that the weight average molecular weight of the polyvinyl alcohol is 100,000 and the alcoholysis degree is 99%.

[0083] Embodiment 11

[0084] The method of this embodiment is the same as that of embodiment 1, except that the weight average molecular weight of the polyvinyl alcohol is 200,000 and the alcoholysis degree is 95%.

[0085] Example 12

[0086] The method of this embodiment is the same as that of embodiment 1, except that the weight average molecular weight of the polyvinyl alcohol is 200,000 and the alcoholysis degree is 89%.

[0087] Embodiment 13

[0088] The method of this embodiment is the same as that of embodiment 1, except that the temperature of the contact reaction is 90°C.

[0089] Embodiment 14

[0090] The method of this embodiment is the same as that of embodiment 1, except that the amount of benzoic anhydride is 0.75 g, and the mass ratio of benzoic anhydride to polyvinyl alcohol is 1:1.3.

[0091] Embodiment 15

[0092] The method of this embodiment is the same as that of embodiment 1, except that the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor in the low eutectic solvent is 1:6.

[0093] Comparative Example 1

[0094] A water-based binder is a commercially available CMC binder (Aladdin, AR).

[0095] Comparative Example 2:

[0096] An oily adhesive is a commercially available PVDF adhesive (Aladdin, AR).

[0097] Comparative Example 3

[0098] The method of this comparative example is the same as that of Example 1, except that the deep eutectic solvent is replaced by dimethyl sulfoxide.

[0099] Comparative Example 4

[0100] The method of this comparative example is the same as that of Example 1, except that benzoic anhydride is replaced by 0.5 g of maleic anhydride.

[0101] Application Examples

[0102] A positive electrode sheet for a lithium-ion battery is prepared, comprising a current collector (Al foil) and a coating loaded on the current collector, wherein the material of the coating comprises a positive electrode active material, lithium iron phosphate, a conductive agent (carbon black SP), and a binder, wherein the binder is the binder provided in Examples 1-12 and Comparative Examples 1 to 4, respectively.

[0103] The preparation method of the positive electrode sheet is as follows: a positive electrode active material (lithium iron phosphate material), a conductive agent carbon black, and a binder are mixed in a mass ratio of 8:1:1, a solvent (water or NMP) is added and fully stirred to make a uniform positive electrode slurry, and the slurry is coated on the positive electrode current collector Al foil with a thickness of 60 μm using a coater, and dried in a drying oven to obtain a positive electrode sheet after drying.

[0104] Test Example 1

[0105] The peel strength of the positive electrode sheet is tested to reflect the strength of the adhesive bond. The test method is as follows: take a sample with a width of 20 mm and a length of 10 mm from the positive electrode sheet; fix the sample with the coating on a stainless steel plate with double-sided tape, and fix the end of the sample that has been peeled off on a tensile probe; perform 180° peeling at a constant speed of 20 mm / min. The peeling force during the peeling process is tested, and the test results are shown in Table 1.

[0106] Test Example 2

[0107] The swelling performance of the binder is characterized by the amount of electrolyte absorbed by the positive electrode. The test method is: cut the positive electrode into discs with a diameter of 25 mm, soak them in the electrolyte for 3 days, weigh the mass of the positive electrode before and after soaking, and the difference between the two is the amount of electrolyte absorption. The ratio of electrolyte absorption to the original weight of the positive electrode is the swelling performance of the positive electrode. The test results are shown in Table 1.

[0108] Table 1

[0109] Binder Adhesion performance / N Swelling performance / % Example 1 9.43 9.8 Example 2 9.61 9.5 Example 3 9.76 9.6 Example 4 9.23 9.1 Example 5 9.41 8.8 Example 6 8.12 8.6 Example 7 8.67 8.2 Example 8 9.11 9.2 Example 9 9.36 8.7 Example 10 8.55 10.1 Embodiment 11 8.01 9.8 Example 12 8.88 9.2 Example 13 9.32 9.7 Embodiment 14 9.46 9.6 Embodiment 15 9.35 9.7 Comparative Example 1 6.11 8.8 Comparative Example 2 2.12 12.3 Comparative Example 3 9.22 9.5 Comparative Example 4 9.38 9.1

[0110] According to the data in Table 1, the modified polyvinyl alcohol aqueous binder disclosed in the present invention has good bonding properties and swelling properties. It can improve the stability and dispersibility of the slurry when applied to the preparation process of lithium-ion battery pole pieces, form a film evenly and completely on the current collector, and prevent the pole piece from falling off during the battery charging and discharging process, which is further beneficial to the cycle stability and rate performance of the lithium-ion battery positive electrode material, thereby extending the service life of the battery.

[0111] Test Example 3

[0112] The electrochemical performance test uses cyclic voltammetry and electrochemical impedance spectroscopy to test the cycle performance, high-power performance and rate performance of lithium batteries. The test results are shown in Table 2. The specific method is as follows:

[0113] Cycle performance: let the assembled battery stand for 10 hours; charge at 0.5C constant current to 4.2V, charge at 4.2V constant voltage to a current less than 0.05mA, and let stand for 5 minutes; discharge at 0.5C constant current to 2.4V, and let stand for 5 minutes; the cycle ends after 200 times.

[0114] High performance: let the assembled battery stand for 10 hours; charge at 5C constant current to 4.2V, charge at 4.2V constant voltage to a current less than 0.05mA, and let stand for 5 minutes; discharge at 5C constant current to 2.4V, and let stand for 5 minutes; the cycle ends after 300 times.

[0115] Rate performance: The prepared positive electrode half-cell was charged to 4.2 V at different rates (0.5C, 1C, 2C, 3C, 5C, 0.5C) with constant current, then switched to 4.2 V constant voltage charging, left for 5 minutes, and then discharged at constant current to a termination voltage of 2.4 V. Each rate was cycled 10 times.

[0116] Cyclic voltammetry: The test was carried out using an electrochemical workstation with a scanning voltage range of 2.4 to 4.2 V and a scanning speed of 1 mV / s.

[0117] Electrochemical impedance spectroscopy: The test was performed using an electrochemical workstation. The amplitude of the disturbance voltage applied during the test was 10 mV and the frequency range was 0.01 Hz-10000 Hz.

[0118] Table 2

[0119]

[0120] According to the data in Table 2, when the aqueous binder of the present invention is used for the positive electrode of a lithium battery, the discharge specific capacity is high, and it has good cycle stability and high rate performance. According to the comparison between Example 1 and Example 3, it can be seen that under the preferred anhydride of the present invention, the aqueous binder prepared is used for the positive electrode of a lithium battery, and the discharge specific capacity is higher, and it has better cycle stability and high rate performance. According to the comparison between Example 1, Example 6, Example 7 and Implementation 8, it can be seen that under the preferred hydrogen bond donor of the present invention, the aqueous binder prepared is used for the positive electrode of a lithium battery, and the discharge specific capacity is higher, and it has better cycle stability and high rate performance. According to the comparison between Example 1 and Example 13, within the temperature range of the contact reaction of the present invention, the aqueous binder prepared is used for the positive electrode of a lithium battery, and the discharge specific capacity is higher, and it has better cycle stability and high rate performance. According to the comparison between Example 1 and Example 4, Example 5, and Example 14, within the preferred mass ratio range of polyvinyl alcohol to anhydride of the present invention, the aqueous binder prepared is used for the positive electrode of a lithium battery, and the discharge specific capacity is higher, and it has better cycle stability and high rate performance. According to the comparison between Example 1 and Example 15, within the molar ratio range of the hydrogen bond acceptor to the hydrogen bond donor of the low eutectic solvent disclosed in the present invention, when the prepared aqueous binder is used for the positive electrode of a lithium battery, the discharge specific capacity is higher, and it has better cycle stability and high rate performance.

[0121] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0122] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0123] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A water-based adhesive, characterized in that: The invention comprises a modified polyvinyl alcohol, wherein the modified polyvinyl alcohol has repeating units as shown in formula (1) and formula (2), Wherein, R1 is selected from one or more of -Ph and -Ph-(R3)n1, each R3 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n1 is any integer between 1 and 5.

2. The aqueous adhesive according to claim 1, wherein The weight average molecular weight of the modified polyvinyl alcohol is 50,000 to 300,000; the molar content of the ester group in the modified polyvinyl alcohol is 5 to 15%.

3. The aqueous adhesive according to claim 1, wherein The aqueous binder is obtained by modifying polyvinyl alcohol with anhydride, wherein the anhydride has a structural formula as shown in formula (3), Wherein, R2 is selected from one or more of -Ph and -Ph-(R4)n2, each R4 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n2 is any integer between 1 and 5; preferably, R4 is selected from one or more of F and Cl, preferably F; and the C1-C3 halogenated hydrocarbon group is selected from one or more of -CF3, -CHF2 and -CH2F, preferably -CF3.

4. The aqueous adhesive according to claim 1, wherein The R3 is selected from one or more of F and Cl, preferably F; the C1-C3 halogenated hydrocarbon group is selected from one or more of -CF3, -CHF2 and -CH2F, preferably -CF3.

5. A method for preparing a water-based binder, characterized in that: The method comprises: Polyvinyl alcohol and anhydride are contacted and reacted in the presence of a low eutectic solvent; the anhydride has a structural formula as shown in formula (3), Wherein, R1 is selected from one or more of -Ph and -Ph-(R3)n1, each R3 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n1 is any integer between 1 and 5; R2 is selected from one or more of -Ph and -Ph-(R4)n2, each R4 is the same or different, and is independently selected from one or more of a halogen atom and a C1-C3 halogenated hydrocarbon group, and n2 is any integer between 1 and 5; R1 and R2 are the same or different.

6. The method according to claim 5, wherein: The alcoholysis degree of the polyvinyl alcohol is 88% to 99%, and the weight average molecular weight of the polyvinyl alcohol is 50,000 to 300,000, preferably 100,000 to 200,000; The acid anhydride is one or more of benzoic anhydride, tetrafluorobenzoic anhydride and 4-trifluoromethylbenzoic anhydride; preferably one or more of tetrafluorobenzoic anhydride and 4-trifluoromethylbenzoic anhydride; The mass ratio of the polyvinyl alcohol to the acid anhydride is 1 to 5:1, preferably 1.5 to 3:

1.

7. The method according to claim 5, wherein: The deep eutectic solvent comprises a hydrogen bond acceptor and a hydrogen bond donor; the hydrogen bond acceptor is a quaternary ammonium salt, and the quaternary ammonium salt is selected from one or more of choline chloride and benzyltriethylammonium chloride, preferably choline chloride; The hydrogen bond donor is selected from one or more of amide, carboxylic acid, urea, thiourea and imidazole, preferably amide and urea; the amide is selected from one or more of formamide, benzamide and trifluoroacetamide, preferably benzamide; the carboxylic acid is selected from one or more of oxalic acid and levulinic acid, preferably oxalic acid; The molar ratio of the hydrogen bond acceptor to the hydrogen bond donor in the deep eutectic solvent is 1:1-5, preferably 1:1-3.

8. The method according to claim 5, wherein: The conditions of the contact reaction include: being carried out in an organic solvent, the contact reaction temperature is 30 to 70° C., preferably 40 to 60° C.; the contact reaction time is 2 to 6 hours, preferably 3 to 5 hours; the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.

9. A water-based binder prepared by the method according to any one of claims 5 to 8.

10. Use of the aqueous binder according to any one of claims 1 to 4 or claim 9 in a lithium ion battery.

11. The use according to claim 10, wherein: The aqueous binder is used for positive electrode plates and / or negative electrode plates of lithium ion batteries.

Citation Information

Patent Citations

  • Preparation and application of binder for negative electrode of lithium ion battery based on tannic acid and derivatives thereof

    CN115172752A

  • Method for preparing cross-linking waterborne adhesive for lithium ion batteries

    CN107793967A

  • Aqueous binder and preparation method and application thereof

    CN111668490A

  • Binder, negative electrode and lithium ion battery

    CN113889621A

  • Modified eutectic solvent, preparation method thereof and lithium ion battery positive electrode material dissolving method

    CN115874056A

Cited By

  • Photo-crosslinked polyacrylic acid-based water-based binder as well as preparation method and application of photo-crosslinked polyacrylic acid-based water-based binder

    CN120349742A

  • A photo-crosslinked polyacrylic acid-based aqueous adhesive and its preparation method and application

    CN120349742B